Quantitative and molecular genetics of child and adolescent mental health disorders: Recent advances, knowledge gaps and directions for future research - Henrik Larsson (Wiley, 2021)
Abstract Quantitative and molecular genetic research studies have already contributed substantially to increase the understanding of the links and boundaries across different child and adolescent mental health conditions and between child and adult forms of psychopathology. Several findings have been replicated across quantitative and molecular genetic methods, and across clinical and population‐based samples. An important task for future quantitative and molecular genetic research is to advance the understanding of how childhood psychopathology unfolds into adult forms of psychopathology, and to reveal the etiologic relationships across different forms of psychopathology. In the years to come, we can expect further breakthroughs in the genetics of child and adolescent mental health disorders to come from converging evidence across different quantitative and molecular genetic methods.